A novel renewable energy-based integrated system with thermoelectric generators for a net-zero energy house - Islam, Shahid; Dincer, Ibrahim; Yilbas, Bekir S. (WILEY, 2020)
A renewable energy based integrated system is developed to meet the total energy demands of a house located off-grid, and a thermodynamic analysis through energy and exergy methodologies is conducted for analysis, evaluation, and performance assessment. The present novel multigeneration system is mainly driven through the animal residues produced at the farm house. The proposed novel system is composed of nine main units namely, a biomass combustor, photovoltaic (PV) panels, parabolic solar trough collectors, thermoelectric generators, organic Rankine cycle, electrolyzer, homogeneous charged compression ignition (HCCI) engine, absorption chiller, and reverse osmosis (RO) unit. Biomass combustor runs an organic Rankine turbine for additional power during peak loads. The exhaust of gas turbine generates cooling to meet the cooling demand of the residential area of the farm house. PV panels are incorporated to generate hydrogen through electrolyzer. A HCCI engine generates power to compensate peak load as well as charging the farming vehicles of the farm house. The RO unit with energy recovery Pelton turbine produces fresh water for farming and residential use. The advanced integration of subsystems, thermoelectric generators and efficient utilization of waste, improves significant amount of energetic and exergetic efficiencies of overall multigenerational system. The energy and exergy efficiencies are enhanced in the order of 4.8% and 6.3%, respectively, after incorporating innovative cooling system to the PV modules. The overall energy and exergy efficiencies of the proposed multigeneration system with and without thermoelectric are found to be 67.6% and 57.1%, and 68.9% and 58.4%, respectively.
Keywords: biomass; efficiency; multigeneration; net-zeroenergy house; renewable energy; solar; OSMOSIS DESALINATION PLANT; PERFORMANCE ASSESSMENT; EXERGY ANALYSES; WET-ETHANOL; POWER-PLANT; HCCI ENGINE; HYDROGEN; CYCLE; OPTIMIZATION; Energy & Fuels; Nuclear Science & Technology